Euthanasia Procedure of Animal Model in Biomedical Research - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Regardless of the method, it is essential to induce unconsciousness as rapidly as possible if euthanasia is to be aesthetically and scientifically successful. Criteria that have been considered in recommending the methods of euthanasia include: time required to produce unconsciousness, time required to produce death, purposes, research results and compliance with the AVMA Guidelines on Euthanasia. There are special considerations for euthanizing rodent embryos, fetuses and neonates.